Writers : their lives and works - Naughtie, James, 1951- (DK Publishing, 2018)
Presents profiles of the world's greatest writers throughout history, including Geoffrey Chaucer, Mary Shelley, Thomas Hardy, William Faulkner, Maya Angelous, and Haruki Murakami.